2022
DOI: 10.3389/feduc.2022.976556
|View full text |Cite
|
Sign up to set email alerts
|

Teachers trust educational science - Especially if it confirms their beliefs

Abstract: Teachers around the world are increasingly required by policy guidelines to inform their teaching practices with scientific evidence. However, due to the division of cognitive labor, teachers often cannot evaluate the veracity of such evidence first-hand, since they lack specific methodological skills, such as the ability to evaluate study designs. For this reason, second-hand evaluations come into play, during which individuals assess the credibility and trustworthiness of the person or other entity who conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 85 publications
0
5
0
1
Order By: Relevance
“…By contrast, it should not only be the practitioners' responsibility to make sense of educational psychologists' findings; it should also be educational psychologists' responsibility to facilitate transferring educational insights into practice. Along this line, scholars have shown that carefully framing and preparing educational insights can indeed lead teachers to trust insights from educational research more than from other sources (Schmidt et al, 2022).…”
Section: Aggregation's Impact On Theory-to-practicementioning
confidence: 99%
“…By contrast, it should not only be the practitioners' responsibility to make sense of educational psychologists' findings; it should also be educational psychologists' responsibility to facilitate transferring educational insights into practice. Along this line, scholars have shown that carefully framing and preparing educational insights can indeed lead teachers to trust insights from educational research more than from other sources (Schmidt et al, 2022).…”
Section: Aggregation's Impact On Theory-to-practicementioning
confidence: 99%
“…Yet the most prevalent misjudgment may be confirmation bias, which refers to the tendency of individuals to seek, interpret, and remember only information that aligns with their preexisting beliefs or expectations while overlooking or dismissing contradictory data [42]. In the field of grading, confirmation bias can exert a substantial influence on teachers' perceptions as they may favor evidence that reinforces their initial judgments of students' capabilities, which may lead, in turn, to an inaccurate assessment of students' true potential [43]. Recognizing the presence of confirmation bias in grading is therefore pivotal for creating fair and objective evaluation systems, allowing educators to mitigate its effects and provide all students with equitable opportunities for learning and growth.…”
Section: Heuristics and Biasesmentioning
confidence: 99%
“…Mistaken beliefs are particularly problematic because they can influence teachers' trust in evidence and shape their initial evaluation of it. Teachers tend to trust evidence more when it is consistent with their prior beliefs than when it contradicts them (Schmidt et al, 2022). Schmidt et al (2022) therefore conclude that the problem does not lie in a general distrust of empirical research, but rather in the fact that (also flawed) beliefs and presuppositions filter and distort the assessment of the credibility of research findings.…”
mentioning
confidence: 98%
“…Teachers tend to trust evidence more when it is consistent with their prior beliefs than when it contradicts them (Schmidt et al, 2022). Schmidt et al (2022) therefore conclude that the problem does not lie in a general distrust of empirical research, but rather in the fact that (also flawed) beliefs and presuppositions filter and distort the assessment of the credibility of research findings. Moreover, prospective teachers often view research as something done by others rather than engaging with it themselves.…”
mentioning
confidence: 98%